Circadian Rhythm of Cardiovascular Disease: The Potential of Chronotherapy With Aspirin - Buurma, Marleen; van Diemen, Jeske J. K.; Thijs, Abel; Numans, Mattijs E.; Bonten, Tobias N. (Frontiers in Cardiovascular Medicine, 2019)
Almost all the systems in our body adhere to a daily 24-h rhythm. The cardiovascular system is also affected by this 24-hour rhythm. In the morning there is a change in various cardiovascular processes, including platelet aggregability. These changes may play a role in the relative excess of early morning cardiovascular events. The number of recurrent cardiovascular diseases (CVD) could, in theory, be reduced by responding to this 24-hour rhythm with timed medication intake (chronotherapy), which also applies to aspirin. Multiple studies on chronotherapy with low-dose aspirin are promising, showing a decrease in early morning platelet activity with evening intake compared with morning intake. However, in order to further demonstrate its clinical impact, randomized trials with cardiovascular events as a primary outcome are needed. This review discusses the available evidence of the effects of circadian rhythm on CVD and the potential positive effect of chronotherapy with aspirin.